GRP-110 Linezolid Adverse Reactions. A One Year Overview. (12th March 2013) - Hernández, J; Serrano de Lucas, L; Baza, B; Baskaran, Z; Sautua, S; de Basagoiti, A; Belaustegi, A; Bilbao, I; Rodriguez, E; Castaño, M
Abstract : Background: Linezolid is an antimicrobial approved for the treatment of hospital or community-acquired pneumonia and complicated skin and soft tissue infections due to Gram positive bacteria. Its use, though effective, is not free from possible harm. Purpose: To describe the incidence and nature of the adverse reactions related to linezolid, taking place before and after the 28-day limit given in the label information. Materials and Methods: All the linezolid treatments over one year (September 2011–September 2012) were recorded. Data sources were the electronic chart as well as the electronic prescription programme. Results: 280 cases were recorded, the median treatment duration being 8 days (1 to 73 days). 4 treatments were interrupted early due to potential interactions with antidepressants. A total of 27 patients developed adverse reactions. Among the 255 patients treated for less than 28 days, 19 developed adverse reactions. 14 presented suppression of at least one myeloid cell line, 7 of them requiring transfusions (one with adverse skin reaction as well). Among the others, two had diarrhoea, one a skin reaction, one vomiting and the remaining patient, asthenia. Median treatment duration in patients with adverse reactions treated for less than 28 days was 12 days (3 to 27 days) 25 patients exceeded 28 days of treatment, 8 of whom had adverse reactions. Seven presented suppression of at least one myeloid cell line, 5 of whom required transfusion. The other patient suffered from asthenia. Median treatment duration in these patients was 37 days (32 to 56 days). Conclusions: Attention should be paid to blood cell counts from the beginning of the treatment, since, as seen, hematologic adverse reactions are not limited to treatments lasting more than 28 days. The same is applicable to other less frequent reactions such as skin reactions, vomiting and asthenia. No conflict of interest.